Eritrea - paths out of isolation - Annette Weber (Stiftung Wissenschaft und Politik (SWP), 2015)
Two decades after achieving independence from Ethiopia, Eritrea is back in the European headlines - above all for a wave of refugees arriving in Europe. At the same time, a recent United Nations Commission on Human Rights report accuses the Eritrean regime of gross human rights violations. President Isayas Afewerki sees Eritrea's regional and international isolation since its war with neighbouring Ethiopia (1998-2000) as evidence of a conspiracy between Ethiopia and influential Western states. Every month between three and five thousand Eritreans attempt to flee the total mobilisation instituted for national defence. Reintegrating the country in regional structures could build trust and neutralise the Eritrean narrative of Ethiopian aggression and international conspiracy. (SWP Comments)
Keywords: 320